Modified nano alpha-aluminum oxide and preparation method thereof

Through microwave hydrothermal method and spray drying technology, the problems of poor dispersion and high calcining temperature of alumina materials are solved, and high purity and easy dispersion nano-α-alumina are prepared, achieving a low-cost and pollution-free production process. Improves the performance and application range of materials.

CN119284927APending Publication Date: 2025-01-10CHANGSHA BEIHE TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411453469.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing composite modified alumina materials have problems such as poor dispersion, difficulty in addition, high calcination temperature, complex operation, high energy consumption and environmental pollution, and their performance is unstable.

Method used

Using microwave hydrothermal method and spray drying technology, the hydrothermal reaction of aluminite powder with organic acids and sintering aids is reduced, the calcination temperature is improved, the spherical morphology and particle size uniformity are improved, and the dispersion and purity of α-alumina are improved. , use a clean high and low temperature ambient box to heat it to ensure the purity of the product.

Benefits of technology

It realizes low-cost, pollution-free preparation of modified nano-α-alumina, and obtains nano-scale particles with uniform particle size, easy to disperse and excellent performance, which is suitable for high-performance ceramics, polishing materials and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284927A_ABST
    Figure CN119284927A_ABST
Patent Text Reader

Abstract

The invention relates to modified nano alpha-aluminum oxide and a preparation method thereof, and belongs to the technical field of new materials. The preparation method of the modified nano alpha-aluminum oxide comprises the following steps: S1, fully mixing a modifier, organic acid and a sintering aid to obtain a pre-solution; s2, adding aluminum stone powder into the pre-solution, and performing hydrothermal reaction after ultrasonic treatment to obtain a mixture; s3, the mixture is subjected to spray drying, calcination, purification and drying, and modified nano alpha-aluminum oxide is obtained; the modifier is one or more of cerium nitrate, cerium acetate, cerium carbonate, silicon tetrachloride, metasilicic acid, sodium silicate, zirconium nitrate, zirconium acetate and butyl titanate. The alpha-aluminum oxide produced by the method is high-purity composite modified nanoscale particles, the particle size is 100-150nm, the particle size distribution is uniform and concentrated, and the alpha-aluminum oxide is easy to disperse; the composition is good, easy to add and stable in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to modified nano alpha-alumina and a preparation method thereof, belonging to the technical field of new materials. Background Art

[0002] Alumina is a widely used chemical inorganic substance with the chemical formula Al2O3. It is a high-hardness compound with a melting point of 2054°C and a boiling point of 2980°C. Currently, there are as many as twelve known crystal forms of alumina, which are allomorphous and heteromorphic. There are three main crystal forms, namely α-alumina, β-alumina and γ-alumina.

[0003] Among them, α-alumina, as alumina with the most stable crystal structure, has the widest application range. However, single α-alumina has certain limitations in various performances during actual application. By composite modification of α-alumina and other materials, modified α-alumina with excellent performance can be obtained, thereby improving the actual use effect.

[0004] At present, most of the composite modified alumina materials are directly composited with alumina and other composite materials and additives under certain conditions, but the nano α-alumina particles obtained in this way often have disadvantages such as poor dispersibility, difficulty in addition, difficulty in modification, and need to be calcined to a high temperature of 1200°C or above. There are also some composite modified alumina materials that are obtained by reacting aluminum salts with acids, alkalis, and alcohols and adjusting the pH value, but this method has complex steps and high energy consumption, is easy to cause environmental pollution, and has poor composite properties and unstable performance.

[0005] CN 113479918 B mixes a spherical amorphous alumina precursor and nano aluminum powder by grinding to obtain a mixture, and then the mixture is subjected to microwave heating and calcination, the calcination temperature is 950-1030°C, and the insulation time is 60-90min. The purpose of the invention is to reduce the formation temperature of the precursor by microwave hydrothermal method, shorten the reaction time, improve the spherical morphology and particle size uniformity of the powder, and obtain a smooth and dense spherical alumina precursor; through microwave calcination technology, rapid and uniform heating is achieved, and the transformation of the spherical morphology to a worm-like structure during the calcination process is reduced; at the same time, by adding nano aluminum powder seeds during microwave calcination, the calcination temperature of α-Al2O3 is further reduced, the dispersibility and uniformity of the spherical α-Al2O3 powder are improved, and the production efficiency is improved. However, the amorphous alumina precursor and aluminum powder of the invention require additional processes to be produced, the cost is relatively high, and the microwave hydrothermal method and microwave-assisted calcination require relatively high energy consumption. Summary of the invention

[0006] The purpose of the present invention is to provide a low-cost, pollution-free modified nano α-alumina and a preparation method thereof.

[0007] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0008] A method for preparing modified nano α-alumina comprises the following steps:

[0009] S1. Fully mix the modifier, organic acid and sintering aid to obtain a pre-solution;

[0010] S2, adding aluminum ore powder to the pre-solution, performing hydrothermal reaction after ultrasonication, and obtaining a mixture;

[0011] S3, spray drying, calcining, purifying and drying the mixture to obtain modified nano α-alumina;

[0012] The modifier is one or more of cerium nitrate, cerium acetate, cerium carbonate, silicon tetrachloride, metasilicic acid, sodium silicate, zirconium nitrate, zirconium acetate, and butyl titanate.

[0013] In a preferred embodiment, the organic acid is one or more of carboxylic acid, oxalic acid, malic acid, citric acid, ascorbic acid, benzoic acid, salicylic acid, caffeic acid, glycine, glutamic acid, and urea.

[0014] The organic acid provides H + Ionic acidic environment is conducive to the completion of the modification reaction.

[0015] In one preferred embodiment, the organic acid is pre-heated and dissolved in ultrapure water.

[0016] The organic acid is pre-dissolved in ultrapure water, which is beneficial for dissolving ionized H + ions, heating increases solubility and accelerates dissolution, thus facilitating the completion of the modification reaction.

[0017] In one preferred embodiment, the heating is performed to a temperature of 75°C to 100°C.

[0018] The temperature is too low and the solubility is low. The ionized H + The lack of ions is not conducive to the adjustment of the pH value of the solution; if the temperature is too high, the aqueous solution will evaporate, which may cause crystal precipitation. Too high a temperature will cause the acidic substances to decompose, resulting in the inability to produce H + Create a good reaction environment.

[0019] At the same time, the role of high temperature is to keep the dissolved substances highly active, making it easier for them to come into contact and react with high-purity aluminum ore powder, making the reaction faster and more uniform.

[0020] The heating method adopts a clean high and low temperature environment box in the clean room to heat or cool to ensure the cleanliness of the water, thereby ensuring the purity of the materials and products.

[0021] In one preferred embodiment, the mass ratio of the organic acid to ultrapure water is 1:(2-10).

[0022] Too much water will cause the concentration (H + ) is too low, the reaction is not good; too little water will lead to insufficient dissolution, containing too much undissolved ionized acidic material, affecting the reaction degree of the composite modifier and aluminum ore powder. Too little water may cause insufficient pressure of the hydrothermal reaction, resulting in insufficient reaction.

[0023] In one preferred embodiment, the mass ratio of aluminum ore powder to organic acid is (2-0.5):1.

[0024] Organic acid is used to change the double electrical layer structure of aluminum ore powder. Too much or too little will affect its solution stability and ball milling efficiency.

[0025] In one preferred embodiment, the mass ratio of the modifier to the aluminum ore powder is (0.2-1.5):10.

[0026] The purpose of the modifier is to improve its surface energy. Too much or too little will affect its dispersibility.

[0027] In one preferred embodiment, the sintering aid is one or more of alumina, zinc fluoride, calcium sulfate, ammonium chloride, ammonium nitrate, and boric acid.

[0028] The sintering aid is used to reduce the calcination reaction temperature and improve the cleanliness of the composite modified material.

[0029] In one preferred embodiment, the mass ratio of the sintering aid to the aluminum ore powder is (0.1-0.5):10.

[0030] In one preferred embodiment, the aluminum stone powder is one or more of high-purity boehmite, pseudo-boehmite, gibbsite, diaspore, boehmite, diaspore and diaspore.

[0031] In one preferred embodiment, if the pre-solution is not fully dissolved, the pre-solution is placed in a ball mill and subjected to ultrasonication, in order to refine the solute in the solution and maintain a good dispersion effect.

[0032] In one preferred embodiment, the temperature of the hydrothermal reaction is 100° C. to 150° C., preferably 130° C.; the pressure is 0.3 to 0.5 MPa; and the time is 6 to 24 hours.

[0033] Under appropriate temperature, time and pressure, the reaction of the present invention is violently activated; on the one hand, the three-dimensional network structure in the gel is enlarged, so that the interlayer and particle spacing are increased; on the other hand, the organic acidic compounds and composite substances are promoted to combine with the formed three-dimensional network structure colloid; and the particles prepared under appropriate temperature, time and pressure are refined, uniform and dispersed, which is convenient for subsequent calcination and reduces the interaction force and hard agglomeration between particles caused by calcination.

[0034] In one of the preferred embodiments, the spray drying process is as follows: the internal pressure is above 0.5 MPa, the temperature of the drying steam is 110°C to 120°C; the inner diameter of the nozzle is 0.5 to 1.0 mm; the solid content of the spray raw material is 10% to 20%; a peristaltic pump is used to extract the sample while stirring; the inlet air temperature is 110°C to 120°C; and the peristaltic feed rate is 480-520 ml / h.

[0035] In one preferred embodiment, the calcination process is: from room temperature to 200°C, the heating rate is 0.5°C ~ 3°C / min; from 200 to 450°C, the heating rate is 3°C ~ 5°C / min; from 450 to 750°C, the heating rate is 5°C ~ 10°C / min; from 750 to 1000°C, the heating rate is 10°C ~ 25°C / min; insulation, the insulation temperature is 800°C ~ 1000°C, and the insulation time is 60 ~ 120min.

[0036] As the furnace body cools down, composite modified nano-alumina is obtained.

[0037] In one preferred embodiment, the equipment used for calcination is a tubular furnace with oxygen gas flow.

[0038] In a preferred embodiment, the purification is to wash the powder obtained after calcination with water, alcohol and centrifugal filtration for multiple times.

[0039] In one preferred embodiment, the drying temperature is 100-150° C., and the water content after drying is not higher than 5 wt %.

[0040] In one preferred embodiment, the particle size of the prepared modified nano α-alumina is 100-150 nm.

[0041] The present invention also claims to protect the modified nano α-alumina prepared by the above preparation method.

[0042] The present invention is further explained below:

[0043] The invention proposes a method for preparing composite modified high-purity nano α-alumina powder, which mainly uses high-purity aluminum stone as raw material, adds organic acidic compounds and composite materials, adopts hydrothermal crystallization reaction and simple high-temperature calcination process, reduces the calcination temperature by adding sintering aids, promotes α-alumina crystal transformation and rapid growth; the α-alumina powder prepared by the method has the characteristics of particle size of 100-200nm, uniform particle size distribution, high purity, easy dispersion, excellent performance, etc. The joint action of aluminum oxide and the composite material enhances general properties such as hardness and compatibility; the production process is simple and the production efficiency is high. The powder is mainly used for polishing materials, additives, ceramic materials, carrier materials, etc., and has good performance.

[0044] The beneficial effects of the present invention are:

[0045] (1) The α-alumina produced by the present invention is a high-purity composite modified nano-scale particle with a particle size of 100-150nm, uniform and concentrated particle size distribution, and easy dispersion; it has good composite properties, is easy to add, and has stable performance.

[0046] (2) The α-alumina powder prepared by the present invention is easy to process and utilize, and can be directly used in the fields of high-performance ceramics, precision polishing, diaphragms, biomedicine or thermal conductive fillers. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The composite modified nano α-alumina is prepared;

[0048] Figure 2 The comparative example prepared is alumina without composite modification. DETAILED DESCRIPTION

[0049] The present invention is further described in detail below in conjunction with examples. However, these examples are limited to illustrating the present invention and are not intended to limit the scope of the present invention. The experimental methods used in the following examples are conventional methods unless otherwise specified, and the reagents, methods and equipment used are conventional reagents, methods and equipment in the art unless otherwise specified.

[0050] Example 1

[0051] Take 450g of ultrapure water and place it in a beaker, heat it to 75℃ in an oven, and keep it warm; take 50g of citric acid and stir and disperse it evenly in ultrapure water, and continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained, and let it stand at 75℃ for 20min. Take 10g of cerium carbonate and mix and disperse it in the solution, stir and disperse it for 40min; then add 1g of aluminum oxide, 2g of zinc fluoride and 1g of boric acid, stir and dissolve for 10min; then use a ball mill to ball mill at 75℃ for 45min at a speed of 180r / min, where the mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 100g of high-purity boehmite powder, slowly add the boehmite powder while stirring the mixture, and keep ultrasonic until all the boehmite is added, continue stirring and ultrasonic dispersion evenly; after mixing evenly, seal the reactor, transfer and place it in an environment of 120℃, the pressure in the reactor is 0.4MPa, and keep it for 12h. The obtained mixture is placed in a spray dryer at 100℃ for drying. The spray drying process is: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110℃~120℃; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; use a peristaltic pump to extract the sample while stirring; the inlet air temperature is 110℃~120℃; the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat, and then placed in a tubular furnace for calcination, and heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, and heated to 1000°C at 25°C / min. The powder is kept at 1000°C for 60 minutes, and then cooled with the furnace. The powder is then washed with water three times, washed with alcohol three times, vacuum dried, and then air flow crushed to obtain a high-purity composite modified α-alumina with an average particle size of 120nm, a relatively uniform particle size distribution, a high sphericity, and a good dispersion effect. Figure 1 shown.

[0052] Example 2

[0053] Take 450g of ultrapure water and place it in a beaker, heat it to 75℃ in an oven, and keep it warm; take 50g of citric acid and stir and disperse it evenly in ultrapure water, and continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained, and let it stand at 75℃ for 20min. Take 10g of cerium nitrate and mix and disperse it in the solution, stir and disperse it for 40min; then add 2g of zinc fluoride, 1g of ammonium nitrate, and 2g of boric acid, and stir and dissolve it for 10min;. Put the evenly dispersed mixture in a reactor and continue to stir and treat it. Take 100g of high-purity boehmite powder, slowly add boehmite powder while stirring the mixture, and keep ultrasonic until all the boehmite is added, and continue to stir and disperse it evenly with ultrasonic; after mixing evenly, seal the reactor, transfer it to an environment of 120℃, and keep the pressure in the reactor at 0.4MPa for 18h. The obtained mixture is placed in a spray dryer at 100°C for drying. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C to 120°C; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; a peristaltic pump is used to extract the sample while stirring; the inlet air temperature is 110°C to 120°C; and the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat and then calcined in a tubular furnace. It is heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, and heated to 950°C at 25°C / min. It is kept at 950°C for 60 minutes and cooled with the furnace. The powder is then washed with water three times and with alcohol three times, and then vacuum dried and air flow crushed to obtain high-purity composite modified α-alumina with an average particle size of 150nm, relatively uniform particle size distribution, high sphericity, and good dispersion effect.

[0054] Example 3

[0055] Take 450g of ultrapure water and place it in a beaker, heat it to 75℃ in an oven, and keep it warm; take 75g of glycine and stir and disperse it evenly in ultrapure water, continue to heat and stir for 15min to dissolve, and let it stand at 75℃ for 20min. Take 15g of tetrabutyl titanate and mix and disperse it in the solution, stir and disperse it for 40min; then add 1g of aluminum oxide, 2g of zinc fluoride, 1g of boric acid and 1g of ammonium chloride, stir and dissolve for 10min; then use a ball mill to ball mill at 75℃ for 45min at a speed of 180r / min, where the mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 150g of high-purity pseudo-boehmite powder, slowly add boehmite powder while stirring the mixture, and keep ultrasonic until all the boehmite is added, continue stirring and ultrasonic dispersion evenly; after mixing evenly, seal the reactor, transfer and place it in an environment of 105℃, the pressure in the reactor is 0.3MPa, and keep it for 24h. The obtained mixture is placed in a spray dryer at 100℃ for drying. The spray drying process is: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110℃~120℃; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; use a peristaltic pump to extract the sample while stirring; the inlet air temperature is 110℃~120℃; the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat and then calcined in a tubular furnace. It is heated to 200°C at a heating rate of 1°C / min, heated to 450°C at 4°C / min, heated to 750°C at 8°C / min, heated to 900°C at 20°C / min, and kept at 900°C for 90 minutes. The powder is cooled in the furnace and then washed with water three times and with alcohol three times. After vacuum drying, it is crushed by air flow to obtain high-purity composite modified α-alumina with an average particle size of 200nm, relatively uniform particle size distribution, high sphericity and good dispersion effect.

[0056] Comparative Example 1

[0057] Take 450g of ultrapure water and place it in a beaker, heat it to 75℃ in an oven, and keep it warm; take 50g of citric acid and stir and disperse it evenly in ultrapure water, and continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained, and stand it at 75℃ for 20min. Then add 1g of aluminum oxide, 2g of zinc fluoride and 1g of boric acid, stir and dissolve for 10min; then use a ball mill to mill for 45min at 180r / min at 75℃, where the mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 100g of high-purity boehmite powder, slowly add boehmite powder while stirring the mixture, and keep ultrasound until all the boehmite is added, and continue to stir and disperse evenly; after mixing evenly, seal the reactor, transfer and place it in an environment of 120℃, and keep the pressure in the reactor at 0.4MPa for 12h. The obtained mixture is placed in a spray dryer at 100°C for drying. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C to 120°C; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; a peristaltic pump is used to extract the sample while stirring; the inlet air temperature is 110°C to 120°C; and the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat, and then placed in a tubular furnace for calcination, and heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, and heated to 1000°C at 25°C / min. The powder is kept at 1000°C for 60 minutes, and then cooled with the furnace. The powder is then washed with water three times and alcohol three times, and then vacuum dried and air flow crushed to obtain uncomposite modified α-alumina particles with worm-like particles, adhesion between particles, poor dispersion, unclear boundaries, and large particles, such as Figure 2 shown.

[0058] Comparative Example 2

[0059] Take 450g of ultrapure water and place it in a beaker, heat it to 120℃ in an oven, and keep it warm; take 50g of ascorbic acid and stir and disperse it evenly in ultrapure water, and continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained, and then stand it at 75℃ for 20min. Take 10g of cerium carbonate and mix and disperse it in the solution, stir and disperse it for 40min; then add 1g of aluminum oxide, 2g of zinc fluoride and 1g of boric acid, stir and dissolve it for 10min; then use a ball mill to mill it at 75℃ for 45min at a speed of 180r / min, where the mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 100g of high-purity boehmite powder, slowly add the boehmite powder while stirring the mixture, and keep ultrasonic until all the boehmite is added, continue stirring and ultrasonic dispersion evenly; after mixing evenly, seal the reactor, transfer and place it in an environment of 120℃, the pressure in the reactor is 0.4MPa, and keep it for 12h. The obtained mixture is placed in a spray dryer at 100℃ for drying. The spray drying process is: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110℃~120℃; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; use a peristaltic pump to extract the sample while stirring; the inlet air temperature is 110℃~120℃; the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat and then calcined in a tubular furnace. It is heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, and heated to 1000°C at 25°C / min. It is kept at 1000°C for 60 minutes and cooled with the furnace. The powder is then washed with water three times, washed with alcohol three times, vacuum dried, and then air flow crushed to obtain α-alumina with larger particles and poor dispersion effect.

[0060] Comparative Example 3

[0061] Take 450g of ultrapure water and place it in a beaker. Heat it to 75℃ in an oven and keep it warm. Take 20g of citric acid and stir and disperse it evenly in ultrapure water. Continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained. Let it stand at 75℃ for 20min. Take 10g of cerium carbonate and mix and disperse it in the solution. Stir and disperse it for 40min. Then add 1g of aluminum oxide, 2g of zinc fluoride and 1g of boric acid and stir and dissolve it for 10min. Then use a ball mill to mill it at 75℃ for 45min at a speed of 180r / min. The mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 100g of high-purity boehmite powder, slowly add the boehmite powder while stirring the mixture, and keep ultrasonic until all the boehmite is added, continue stirring and ultrasonic dispersion evenly; after mixing evenly, seal the reactor, transfer and place it in an environment of 120℃, the pressure in the reactor is 0.4MPa, and keep it for 12h. The obtained mixture is placed in a spray dryer at 100℃ for drying. The spray drying process is: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110℃~120℃; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; use a peristaltic pump to extract the sample while stirring; the inlet air temperature is 110℃~120℃; the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat and then calcined in a tubular furnace. It is heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, and heated to 1000°C at 25°C / min. It is kept at 1000°C for 60 minutes and cooled with the furnace. The powder is then washed with water three times and with alcohol three times, vacuum dried, and then air flow crushed to obtain α-alumina with a large number of large particles, uneven distribution of large and small particles, and a large span of particle sizes.

[0062] Comparative Example 4

[0063] Take 450g of ultrapure water and place it in a beaker, heat it to 75℃ in an oven, and keep it warm; take 50g of citric acid and stir and disperse it evenly in ultrapure water, and continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained, and let it stand at 75℃ for 20min. Take 10g of cerium carbonate and mix and disperse it in the solution, stir and disperse it for 40min; then add 1g of aluminum oxide, 2g of zinc fluoride and 1g of boric acid, stir and dissolve for 10min; then use a ball mill to ball mill at 75℃ for 45min at a speed of 180r / min, where the mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 400g of high-purity boehmite powder, slowly add the boehmite powder while stirring the mixture, and keep ultrasonic until all the boehmite is added, continue stirring and ultrasonic dispersion evenly; after mixing evenly, seal the reactor, transfer and place it in an environment of 120℃, the pressure in the reactor is 0.4MPa, and keep it for 12h. The obtained mixture is placed in a spray dryer at 100℃ for drying. The spray drying process is: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110℃~120℃; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; use a peristaltic pump to extract the sample while stirring; the inlet air temperature is 110℃~120℃; the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat and then calcined in a tubular furnace. It is heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, and heated to 1000°C at 25°C / min. It is kept at 1000°C for 60 minutes and cooled with the furnace. The powder is then washed with water three times and with alcohol three times, vacuum dried, and then air flow crushed to obtain α-alumina with large micron-sized particles, uneven particle distribution, and incomplete modification.

[0064] Comparative Example 5

[0065] Take 450g of ultrapure water and place it in a beaker. Heat it to 75℃ in an oven and keep it warm. Take 50g of citric acid and stir and disperse it evenly in ultrapure water. Continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained. Let it stand at 75℃ for 20min. Take 0.5g of cerium carbonate and mix and disperse it in the solution. Stir and disperse it for 40min. Then add 1g of aluminum oxide, 2g of zinc fluoride and 1g of boric acid and stir and dissolve for 10min. Then use a ball mill to mill at 75℃ for 45min at a speed of 180r / min. The mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 100g of high-purity boehmite powder, slowly add the boehmite powder while stirring the mixture, and keep ultrasonic until all the boehmite is added, continue stirring and ultrasonic dispersion evenly; after mixing evenly, seal the reactor, transfer and place it in an environment of 120℃, the pressure in the reactor is 0.4MPa, and keep it for 12h. The obtained mixture is placed in a spray dryer at 100℃ for drying. The spray drying process is: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110℃~120℃; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; use a peristaltic pump to extract the sample while stirring; the inlet air temperature is 110℃~120℃; the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat and then calcined in a tubular furnace. It is heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, and heated to 1000°C at 25°C / min. It is kept at 1000°C for 60 minutes and cooled with the furnace. The powder is then washed with water three times and with alcohol three times, vacuum dried, and then air flow crushed to obtain α-alumina with a partial worm-like structure, partial large particles, small particles sticking together, and uneven distribution.

[0066] Comparative Example 6

[0067] Take 450g of ultrapure water and place it in a beaker, heat it to 75℃ in an oven, and keep it warm; take 50g of citric acid and stir and disperse it evenly in ultrapure water, and continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained, and stand it at 75℃ for 20min. Take 10g of cerium carbonate and mix and disperse it in the solution, stir and disperse it for 40min; then add 1g of aluminum oxide, 2g of zinc fluoride and 1g of boric acid, stir and dissolve it for 10min; then use a ball mill to mill it at 75℃ for 45min at a speed of 180r / min, where the mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 100g of high-purity boehmite powder, slowly add boehmite powder while stirring the mixture, and keep ultrasound until all the boehmite is added, and continue to stir and disperse it evenly; after mixing evenly, seal the reactor, transfer it to an environment of 250℃, and keep the pressure in the reactor at 1MPa for 12h. The obtained mixture is placed in a spray dryer at 100°C for drying. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C to 120°C; the inner diameter of the nozzle is 1.0mm; the solid content of the spray raw material is 20%; a peristaltic pump is used to extract the sample while stirring; the air inlet temperature is 110°C to 120°C; the peristaltic feed rate is 500ml / h. The completely dried powder is placed in a porcelain boat, and then placed in a tubular furnace for calcination, and heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, heated to 1000°C at 25°C / min, and kept at 1000°C for 60min, cooled with the furnace, and then the powder is washed with water three times, washed with alcohol three times, vacuum dried, and air flow crushed to obtain α-alumina with small particles bonding, uneven distribution, and irregular morphology.

[0068] Comparative Example 7

[0069] Take 450g of ultrapure water and place it in a beaker, heat it to 75℃ in an oven, and keep it warm; take 50g of citric acid and stir and disperse it evenly in ultrapure water, and continue to heat and stir for 15min to dissolve until a clear and transparent solution is obtained, and let it stand at 75℃ for 20min. Take 10g of cerium carbonate and mix and disperse it in the solution, stir and disperse it for 40min; then add 1g of aluminum oxide, 2g of zinc fluoride and 1g of boric acid, stir and dissolve for 10min; then use a ball mill to ball mill at 75℃ for 45min at a speed of 180r / min, where the mass ratio of zirconium beads to the mixture is 1:5. Put the ball-milled mixture in a reactor and continue to use ultrasound for ultrasonic dispersion treatment. Take 100g of high-purity boehmite powder, slowly add the boehmite powder while stirring the mixture, and keep ultrasonicating until all the boehmite is added, and continue stirring and ultrasonicating to disperse evenly; after mixing evenly, seal the reactor, transfer and place it in an environment of 120℃, and the pressure in the reactor is 0.4MPa, which is maintained for 12h. The obtained mixture is placed in a spray dryer at 180°C for drying. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C-120°C; the inner diameter of the nozzle is 1.5mm; the solid content of the spray raw material is 20%; a peristaltic pump is used to extract samples while stirring; the inlet air temperature is 110°C-120°C; the peristaltic feed rate is 1000ml / h. The completely dried powder is placed in a porcelain boat, and then placed in a tubular furnace for calcination, and is heated to 200°C at a heating rate of 2°C / min, heated to 450°C at 5°C / min, heated to 750°C at 10°C / min, heated to 1000°C at 25°C / min, and kept at 1000°C for 60min, cooled with the furnace, and then the powder is washed with water three times and alcohol three times, and then air flow crushed after vacuum drying to obtain α-alumina with large particles, small particles bonding, porous plate structure and uneven distribution.

[0070] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0071] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing modified nano α-alumina, characterized in that: The following steps are involved: S1. Fully mix the modifier, organic acid and sintering aid to obtain a pre-solution; S2, adding aluminum ore powder to the pre-solution, performing hydrothermal reaction after ultrasonication, and obtaining a mixture; S3, spray drying, calcining, purifying and drying the mixture to obtain modified nano α-alumina; The modifier is one or more of cerium nitrate, cerium acetate, cerium carbonate, silicon tetrachloride, metasilicic acid, sodium silicate, zirconium nitrate, zirconium acetate, and butyl titanate.

2. The preparation method according to claim 1, characterized in that: The organic acid is one or more of carboxylic acid, oxalic acid, malic acid, citric acid, ascorbic acid, benzoic acid, salicylic acid, caffeic acid, glycine, glutamic acid, and urea.

3. The preparation method according to claim 1, characterized in that: The organic acid is pre-heated and dissolved in ultrapure water; preferably, the temperature is heated to 75°C to 100°C.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the organic acid to the ultrapure water is 1:(2-10); the mass ratio of the aluminum ore powder to the organic acid is (2-0.5):

1.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the modifier to the aluminum ore powder is (0.2-1.5):

10.

6. The preparation method according to claim 1, characterized in that: The sintering aid is one or more of aluminum oxide, zinc fluoride, calcium sulfate, ammonium chloride, ammonium nitrate, and boric acid; preferably, the mass ratio of the sintering aid to aluminum stone powder is (0.1-0.5):

10.

7. The preparation method according to claim 1, characterized in that: The diaspore powder is one or more of high-purity boehmite, pseudo-boehmite, gibbsite, diaspore, boehmite, diaspore and diaspore.

8. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100° C. to 150° C., preferably 130° C.; the pressure is 0.3 to 0.5 MPa; and the time is 6 to 24 hours.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The calcination process is as follows: from room temperature to 200°C, the heating rate is 0.5°C to 3°C / min; from 200 to 450°C, the heating rate is 3°C to 5°C / min; from 450 to 750°C, the heating rate is 5°C to 10°C / min; from 750 to 1000°C, the heating rate is 10°C to 25°C / min; heat preservation, the heat preservation temperature is 800°C to 1000°C, and the heat preservation time is 60 to 120min.

10. The modified nano α-alumina prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for preparing nano-spherical α-alumina powder

    CN113479918B